Роль 3D-моделювання у подоланні викликів дистанційного навчання - Дереза, Олена Олександрівна; Dereza, Olena; Водяницький, Іван Олексійович; Vodyanitskyi, Ivan (Запоріжжя : ТДАТУ, 2025)
UA: Стаття присвячена особливостям використання 3D-технологій у закладах вищої освіти України. Проаналізовані проблеми й виклики підготовки майбутніх фахівців технічних спеціальностей під час дистанційного навчання. Визначено, що значне місце та роль у системі вищої освіти набувають поєднання комп’ютерних засобів навчання з традиційними. /// EN: The article is devoted to the features of the use of 3D technologies in higher education institutions of Ukraine. The problems and challenges of training future specialists in technical specialties during distance learning are analyzed. It is determined that a significant place and role in the higher education system is acquired by the combination of computer-based learning tools with traditional ones.
The role of 3D modeling in overcoming the challenges of distance learning
Keywords: комп’ютерне моделювання; просторове мислення; 3D- технології; програмне забезпечення; computer modeling; spatial thinking; 3D technologies; software